Application of specialised knowledge in the course of investigation of criminal offences committed in the field of consumer goods production - V. D. Pcholkin; A. I. Muradly (Bulletin of Kharkiv National University of Internal Affairs)
The article examines the theoretical, regulatory, legal and scientific-methodological foundations of the special knowledge application in the course of criminal offences investigation. The author focuses on the scientific debate on the definition of special knowledge and its correlation with forensic knowledge. The views of scholars who have made attempts to formulate the concept of "special knowledge" have been analysed, and the shortcomings of the legal regulation of special knowledge in the legislative acts of Ukraine have been identified. It has been supported that the concept of “special knowledge” should be formulated by scientists, since legislative acts do not disclose its content.